Continuum dynamics and statistical correction of compositional heterogeneity in multivalent IDP oligomers resolved by single-particle EM. Issue 9 (15th May 2022) - Mostofian, Barmak; McFarland, Russell; Estelle, Aidan; Howe, Jesse; Barbar, Elisar; Reichow, Steve L.; Zuckerman, Daniel M.
Graphical abstract: Highlights: Semi-ordered multivalent IDPs are highly prevalent complexes in the cell. These difficult targets studied by novel single-particle EM distribution analysis. Conformational and compositional heterogeneity disentangled and quantified. Validated and applied to multivalent IDPs bound to the universal hub protein, LC8. This automated approach may be applied to other IDP systems. Abstract: Multivalent intrinsically disordered protein (IDP) complexes are prevalent in biology and act in regulation of diverse processes, including transcription, signaling events, and the assembly and disassembly of complex macromolecular architectures. These systems pose significant challenges to structural investigation, due to continuum dynamics imparted by the IDP and compositional heterogeneity resulting from characteristic low-affinity interactions. Here, we developed a modular pipeline for automated single-particle electron microscopy (EM) distribution analysis of common but relatively understudied semi-ordered systems: 'beads-on-a-string' assemblies, composed of IDPs bound at multivalent sites to the ubiquitous ∼20 kDa cross-linking hub protein LC8. This approach quantifies conformational geometries and compositional heterogeneity on a single-particle basis, and statistically corrects spurious observations arising from random proximity of bound and unbound LC8. The statistical correction is generically applicable to oligomer characterization and not specific to our pipeline. Following validation, the approach was applied to the nuclear pore IDP Nup159 and the transcription factor ASCIZ. This analysis unveiled significant compositional and conformational diversity in both systems that could not be obtained from ensemble single particle EM class-averaging strategies, and new insights for exploring how these architectural properties might contribute to their physiological roles in supramolecular assembly and transcriptional regulation. We expect that this approach may be adopted to many other intrinsically disordered systems that have evaded traditional methods of structural characterization.